A summary of TCRP Report 88 A guidebook for developing a transit performance-measurement system. - Ryus, Paul.; United States. Federal Transit Administration; Transit Cooperative Research Program; National Research Council (U.S.). Transportation Research Board; Kittelson & Associates, Inc. ([Washington, D.C.] Transportation Research Board, 2003)
"This summary was prepared by Paul Ryus, principal investigator, Kittelson & Associates, Inc."
Caption title.
"Sponsored by the Federal Transit Administration."
"January 2003."
Includes bibliographical references (p. 25).
Also available online via the TRB web site (www.trb.org).
Keywords: Local transit -- Evaluation; Local transit -- Management; Local transit -- Cost effectiveness; Organizational effectiveness; Local transit -- United States -- Performance